A Study of Connected Vehicle for Vehicle Maintenance - Yogarayan, Sumendra; Azman, Afizan; Fatimah Abdul Razak, Siti; Jai Raman, Kirbana; Fikri Azli Abdullah, Mohd; Zainab Ibrahim, Siti; Sonai Muthu, Kalaiarasi (International Journal of Engineering and Technology, 2018)
Connected Vehicle Maintenance System is a system that is developed to assist car owners from facing problems especially when there is a vehicle breakdown. Vehicles in Malaysia do not have any available platform system that can provide assistance, diagnostic and telematics services to car owners. As vehicles are connected with various components of vehicle control unit, huge number of data are generated. Gathering this data has become a part of the connected vehicle research scope. However, car owners do not understand raw vehicle data unless their vehicles are brought to a service center. Thus, enabling in-vehicle system to interpret and monitor this data is an advancement of technology and provides a convenient driving environment for car owners. Â Â